Synthesis and Biological Evaluation of Some New Chalcones Containing 2,5-Dimethylfuran Moiety - S. Sridhar; S. C. Dinda; Y. Rajendra Prasad (E-Journal of Chemistry)
A series of new chalcones (3a-g) were prepared by Claisen-Schmidt condensation of 3-acetyl-2,5-dimethylfuran with various substituted aromatic aldehydes in presence of aqueous solution of potassium hydroxide and ethanol at room temperature. The synthesized chalcones were characterized by means of their IR, 1H NMR spectral data and elemental analyses. When these chalcones were evaluated for antimicrobial and anti-inflammatory activities, some of them were found to possess significant activity, when compared to standard drugs.